High prevalence of recreational and illicit drug use in German people living with HIV with a potential for drug–drug interactions with antiretroviral therapy. (January 2021) - Funke, B; Spinner, CD; Esser, S; Stellbrink, HJ; Stoehr, A; Wolf, E; Koegl, C; Bruening, J; Witte, V
Recreational drug use is higher in people living with HIV (PLHIV) than in the general population in Europe. This use increases the risk for drug-drug interactions (DDIs) and adverse events. We assessed the prevalence and clinical consequences of substance abuse among PLHIV. BESIDE was a cross-sectional, multi-center study in 2016/18, evaluating comorbidities, polypharmacy and recreational/illicit drug use in PLHIV on antiretroviral therapy (ART) in Germany. Legal and illicit drug use was recorded using two anonymous patient questionnaires one year apart (Q1 and Q2). The BESIDE study population consisted of 453 PLHIV (22% female, median age 46 years). Recreational drug use was reported by the majority (Q1: ever used 73%, within previous 6 months 56%): nitrite inhalants ("poppers"), cannabis and PDE-5 inhibitors were common across all age groups; ecstasy, (meth-)amphetamine and gamma-hydroxybutyrate/gamma-butyrolactone were predominantly reported by younger PLHIV. Based on Q2, two-thirds of PLHIV (67%) had been informed about potential risks of drug abuse by their doctors, whereas one-third (33%) had talked to their doctors on their own initiative with only 7% considering drug use in combination with ART a problem. Strikingly, 44% and 42% had undergone medical treatment or had been hospitalized due to drug use. These data emphasize the high clinical relevance of recreational drug use in PLHIV and the need for treating physicians to pro-actively communicate the potential risks.